2018
DOI: 10.3847/2041-8213/aab429
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Model for Tidal Disruption Events

Abstract: In the past few years wide-field optical and UV transient surveys as well as X-ray telescopes have allowed us to identify a few dozen candidate tidal disruption events (TDEs). While in theory the physical processes in TDEs are expected to be ubiquitous, a few distinct classes of TDEs have been observed. Some TDEs radiate mainly in NUV/optical while others produce prominent X-rays. Moreover, relativistic jets have been observed in only a handful of TDEs. This diversity might be related to the details of the sup… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
410
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(473 citation statements)
references
References 137 publications
35
410
3
Order By: Relevance
“…An optically-thick extended envelope may form from stellar debris around the black hole, reprocessing a fraction of the X-ray accretion flare into the UV and optical bands (eg. Loeb & Ulmer 1997;Ulmer et al 1998), with the extent of reprocessing potentially viewing angle dependent (Roth et al 2016;Dai et al 2018). As we are interested in exploring eROSITA's sensitivity to the X-ray signatures of WTDEs, we keep to this simplified model of emission from the event and ignore reprocessing in this work (further discussion in section 5.2).…”
Section: Spectral Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…An optically-thick extended envelope may form from stellar debris around the black hole, reprocessing a fraction of the X-ray accretion flare into the UV and optical bands (eg. Loeb & Ulmer 1997;Ulmer et al 1998), with the extent of reprocessing potentially viewing angle dependent (Roth et al 2016;Dai et al 2018). As we are interested in exploring eROSITA's sensitivity to the X-ray signatures of WTDEs, we keep to this simplified model of emission from the event and ignore reprocessing in this work (further discussion in section 5.2).…”
Section: Spectral Propertiesmentioning
confidence: 99%
“…On the other hand, the WTDE detection rate may be lowered by reprocessing of X-rays by optically thick outflows, predicted to be launched for cases of super Eddington fallback rates. Dai et al (2018) propose a unified model of TDEs, whereby the viewing angle of the TDE affects whether one observes optical or X-ray dominated emission due to the angular dependence of the outflow's density. When viewed face on, one probes X-ray emission from the inner accretion disc, whereas a larger amount of X-ray radiation is reprocessed (due to increasing photoelectric absorption in the outflow density) with increasing viewing angle.…”
Section: Tde Modelingmentioning
confidence: 99%
“…Some of the disrupted material is then accreted onto the SMBH, producing a bright optical/UV/X-ray transient that fades over time. The relative amounts of accreted and ejected material, as well as the properties of the transient, are a combination of various physical processes, such as geometry of the original orbit (e.g., Guillochon & Ramirez-Ruiz 2013;Dai et al 2018), the properties of both the disrupted star and SMBH (e.g., Guillochon & Ramirez-Ruiz 2013;Kochanek 2016), and radiative feedback from the accretion (e.g., Gaskell & Rojas Lobos 2014;Strubbe & Murray 2015;Roth et al 2016;Roth & Kasen 2018). Previous studies of TDEs (e.g., Holoien et al 2014;Auchettl et al 2017) generally found that the energy radiated during the events are of order 10 51 erg with mass equivalents of less than 0.01 M assuming an accretion efficiency of η = 0.1, suggesting that most of the bound debris is ejected and not accreted, or that the accretion efficiency is lower than expected.…”
Section: Introductionmentioning
confidence: 99%
“…Dai et al (2018) proposed a unified model of TDE and pointed out that the different emission may be caused by the different viewing angles. Dai et al (2018) also studied the disk dynamics of the TDE through general relativistic radiation magnetohydrodynamic simulations, and proposed that a jet can be produced. If a jet does exist in a TDE, the observations would be subject to the beaming effect.…”
Section: Introductionmentioning
confidence: 99%